2007
DOI: 10.1127/0935-1221/2007/0019-0095
|View full text |Cite
|
Sign up to set email alerts
|

Fluorcalciobritholite, (Ca,REE)5[(Si,P)O4]3F, a new mineral: description and crystal chemistry

Abstract: The new mineral fluorcalciobritholite, ideally Ca 3 Ce 2 (SiO 4) 2 (PO 4)F, has been found at Mount Kukisvumchorr, Khibiny alkaline complex, Kola Peninsula, Russia, in veinlets which contains aggregates of orthoclase, nepheline, sodalite and biotite in association with grains of fayalite, gadolinite-(Ce), zircon, monazite-(Ce), zirconolite ("polymignite"), fluorapatite, fluorite, molybdenite, löllingite and graphite. Fluorcalciobritholite forms long-prismatic hexagonal crystals up to 0.5 x 10 mm; the main crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…BGM are locally enriched in actinide elements, particularly in Th and less in U which are the regular source of their metamictization. Thorium content in britholite-(Ce), fluorbritholite-(Ce), and fluorcalciobritholite compositions with Ce N Y can reach~3 to 23 wt.% ThO 2 or 0.06 to 0.68 apfu (Contini et al, 1993;Della Ventura et al, 1999;Melluso et al, 2010;Oberti et al, 2001;Orlandi et al, 1989;Pekov et al, 2007). In contrast, BGM compositions with Y N Ce contain notably lesser Th (up to~2 wt.% ThO 2 ; Griffin et al, 1979;Payette and Martin, 1986;Pekov et al, 2011;Smith et al, 2002).…”
Section: Composition and Formation Of Britholite Group Mineralsmentioning
confidence: 99%
See 2 more Smart Citations
“…BGM are locally enriched in actinide elements, particularly in Th and less in U which are the regular source of their metamictization. Thorium content in britholite-(Ce), fluorbritholite-(Ce), and fluorcalciobritholite compositions with Ce N Y can reach~3 to 23 wt.% ThO 2 or 0.06 to 0.68 apfu (Contini et al, 1993;Della Ventura et al, 1999;Melluso et al, 2010;Oberti et al, 2001;Orlandi et al, 1989;Pekov et al, 2007). In contrast, BGM compositions with Y N Ce contain notably lesser Th (up to~2 wt.% ThO 2 ; Griffin et al, 1979;Payette and Martin, 1986;Pekov et al, 2011;Smith et al, 2002).…”
Section: Composition and Formation Of Britholite Group Mineralsmentioning
confidence: 99%
“…Occurrences of primary magmatic BGM are limited to peralkaline granites and syenite pegmatites (e.g., Griffin et al, 1979;Larsen, 1996;Pekov et al, 2007Pekov et al, , 2011Vilalva et al, 2013) or peralkaline rhyolitic rocks (Min et al, 2006;Payette and Martin, 1986). Formation of BGM is usually connected with late-to post-magmatic or hydrothermal alteration processes in diverse alkaline rocks, for example, in alkali syenitic ejecta (Della Ventura et al, 1999), REE-enriched pegmatite segregations (Arden and Halden, 1999), carbonate-amphibole-clinopyroxene rocks (Zaitsev and Chakhmouradian, 2002), REE-rich mineralized zones associated with potassic alkaline to subalkaline volcanic to plutonic rocks (Harlov et al, 2003), or carbonatites and related skarn deposits (Ahijado et al, 2005).…”
Section: Composition and Formation Of Britholite Group Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the occurrence of allanite-(Ce) and fluorbritholite-(Ce) with significant aegerine-augite, titanite, and apatite, but without monazite-(Ce), in their study area differs from the mineral assemblages at Jamestown. Whereas the Jamestown mineralization is associated with an anorogenic peraluminous granite intrusion (two-mica monzo-to syenogranite), the few other known localities with fluorbritholite are associated with alkaline (e.g., Della Ventura et al 1999;Liferovich and Mitchell 2006;Pekov et al 2007), peralkaline (agpaitic; e.g., Jiexiang et al 1994;Sørensen 1997), and carbonatite intrusions (e.g., Feldman et al 1987). Pekov et al (2007) describe the mineral and its holotype occurrence on Mount Kukisvumchorr in the Kola Peninsula in Russia, where it appears as veinlets in fenitized gneiss xenoliths.…”
Section: Rare Mineralsmentioning
confidence: 99%
“…The minerals were identified in the alkali and felsic magmatic rocks, as well as in the metasomatites and pegmatites associated with subalkali and alkali granites, alkali, and nepheline syenites, and carbon atites (Kolyago and Lapin, 1990;Mel'nikov and Gre chanovskaya, 2010;Ripp et al, 2005;Arden and Halden, 1999;Della Ventura et al, 1999;Griffin et al, 1979;Gu et al, 1994;Orlandi et al, 1989;Pekov et al, 2007Pekov et al, , 2011Uher and Ondrejka, 2008). It is suggested that britholite in most of the occurrences was crystal lized at the late to postmagmatic (pegmatite and hydro thermal) stages.…”
Section: Introductionmentioning
confidence: 99%